The Importance of Using Plant Resources During COVID-19 Pandemics to Mitigate Daily Needs and Some Diseases - Luo, Binsheng; Bhatt, Arvind (Frontiers in Public Health, 2022)
At the end of 2019, the coronavirus virus COVID-19 has brought the whole world a serious disaster. During this special time, some rural communities were least affected by the epidemic, mainly reflected on the rational utilization of natural biological resources, including edible and medicinal plants and the management of the home gardens. This paper deconstructed the self-responses of rural communities during the pandemic time and tried to provide some suggestions for local government on policymaking. In the end, the future development of ethnobiology in China has been discussed.